2013
DOI: 10.1007/s10552-013-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between statin use and colorectal cancer risk: a meta-analysis of 42 studies

Abstract: Our results suggest that statin use is associated with a modest reduced risk of CRC; apparent associations were found for lipophilic statin use. However, long-term statin use did not appear to significantly affect the risk of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 74 publications
1
94
2
Order By: Relevance
“…Any benefit from lifestyle changes can be augmented by regular intake of aspirin and other nonsteroidal anti-inflammatory drugs 33 ; however, this effect seems to depend on host genotype 34,35 . Statin use might have a small preventive effect on colorectal cancer incidence 36,37 , as does hormone therapy in post-menopausal women 38 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Any benefit from lifestyle changes can be augmented by regular intake of aspirin and other nonsteroidal anti-inflammatory drugs 33 ; however, this effect seems to depend on host genotype 34,35 . Statin use might have a small preventive effect on colorectal cancer incidence 36,37 , as does hormone therapy in post-menopausal women 38 .…”
Section: Epidemiologymentioning
confidence: 99%
“…They are among the most commonly used drugs for treatment of hypercholesterolemia and reduction of cardiovascular risk 22 . However studies have suggested an intriguing potential benefit by reducing cancer incidence, in particular, colorectal cancer 2225 . Most prior studies have focused on sporadic colon cancer with only one prior study demonstrating an inverse association between statin use and IBD-related neoplasia 26 .…”
Section: Introductionmentioning
confidence: 99%
“…We were also not convinced that there would be a sufficient number of initiators in the data. Statins were excluded because there is ongoing debate as to whether they are associated with cancer risk[65, 66]. There is a substantial body of evidence on anti-hypertensives (AHT), enough to state with some certainty that they do not dramatically alter CRC risk, and limited evidence that some may reduce risk[67], with the exception of beta-blockers where evidence suggests a reduced cancer risk[68].…”
Section: Case Study: Antidepressants and Colorectal Cancermentioning
confidence: 99%